Effect of Mechanical Activation on the Barite Carbothermic Reduction - Ordonez, S (2012)
In this work the effect of mechanical activation on the barite carbothermic reduction has been investigated. The mechanical activation of barite and coke was carried out in a SPEX 8000 D mill. The microstructural and morphological characterization of the powders was obtained by X-ray diffraction and scanning electron microscopy. The kinetics of barite carbothermic reduction was studied using differential scanning calorimetry and thermogravimetry. The experimental results revealed that the mechanical activation process improves the kinetics of barite carbothermic reduction. It was found that 3.6 ks of milling decreases the activation energy of barite reduction from 519 to 276 kJ/mol. This behavior can be explained considering the increase of reactants enthalpy due to the energy stored by the powders and the intimate contact between fine barite and coke particles promoted by the milling process. © 2011 Elsevier B.V. All rights reserved.